Gameful Experience and Brand Loyalty: Exploring Customer Brand Engagement in Language Learning Apps - Penampe, Marie Anne Ester; Fitriana, Ana; Purnomo, Bintoro Bagus; Afiah, Nur; Juniwati, Juniwati (Journal of Applied Management Research, 2024)
This study examines the impact of gameful experiences on brand loyalty in language learning applications mediated by customer brand engagement. With the increasing incorporation of gamification in educational tools, understanding how specific game mechanics drive user engagement and brand loyalty in language learning apps is crucial. While existing gamification research generally focuses on broader fields, this study uniquely investigates how specific gameful experiences—such as enjoyment, creative thinking, and domination—affect brand loyalty in the context of language learning applications. Data were collected from 250 active users in Indonesia using an online survey with a Likert scale of 1-5, employing purposive sampling. Structural Equation Modeling (SEM) with AMOS 26 assessed validity, reliability, and relationships among variables. The results indicate that gameful experiences significantly enhance customer brand engagement, which, in turn, positively influences brand loyalty. This study contributes new insights into how gamification affects brand loyalty, specifically in the language learning app domain, providing practical recommendations for developers to incorporate effective game mechanics to enhance customer brand engagement and foster long-term brand loyalty.